Consorciação gramínea - leguminosa em pastejo intensivo: parâmetros de solo, planta e animal - Thasia Martins Macêdo (2015)
The objective was to observe and describe aspects intercropping between grasses and legumes, with the plant and soil characteristics along with animal performance in a period of one year, integrated with palisade grass pasture (Urochloa brizantha) and herbaceous forage peanut cv. Belmonte (Arachis pintoi), and marandu grass fertilize grass with 120 kg nitrogen/ ha located in the Animal Science Experimental Station, the city of Itabela, extreme south of Bahia. The experimental area of 8 ha divided into 48 paddocks with 24 paddocks of marandu grass intercropped with peanuts and 24 paddocks of grass marandu fertilized, established more than 10 years. Were made, measurements every 28 days during all the season, forage allowance, forage height, soil collection, weighing the body weight of the steers, and chemical analyzes of soil and grass bromatological analysis, in vitro digestibility forage. There was interaction between stations and the type of crop to plant height variable in the pre-grazing (P<0.05). For both treatments canopy height was higher in fall and in other similar stations. For both treatments canopy height was higher in fall and in other similar stations. Treatment with legume most post-grazing forage mass occurred during the summer, followed by no significant reduction in the fall and winter, showing significant difference (P<0.01) in the spring compared to the summer. For the area fertilized with nitrogen to forage mass was similar throughout the year (P>0.05). The intercropping of legumes with graminea influenced the stocking rate, gain Daily animal's weight and the gain by area. The surface layers of both systems tended to present lower values of soil density. The pH of the water was different (P<0.05) between the depths of the types of crops and intercropped was lower (P<0.05) in the first depth analyzed in relation to the areas fertilized with nitrogen. From the depth of 20-40 cm and intercropped fertilized areas were similar.